Students’ evaluation of preclinical simulation for all ceramic preparation (In Faculty of Dentistry Universiti Kebangsaan Malaysia) - Natasya Ahmad Tarib; Marlynda Ahmad (Dental Journal (Majalah Kedokteran Gigi), 2008)
The purpose of the study is to evaluate all ceramic crown (ACC) preparations those were made by dental undergraduate students during the preclinical sessions. 104 plastic teeth were prepared by 4th year dental undergraduates during the preclinical session for ACC crown examined. The teeth were placed on the frasaco arches and were mounted in the frasaco head. The preparations were examined for the tapering, presence of undercuts, incisal and cingulum reductions as well as preparation of shoulder margin. Preparations were examined using hand instruments and visual. The sample size was 92 plastic teeth. Most of the preparations were acceptable with acceptable placement and types of margins, adequate axial and incisal reductions and acceptable tapered of the axial walls. On the other hand, most of the teeth showed absence of cingulum wall. Most of the crowns prepared by the students were acceptable. It showed that they understood the principles of crown preparation. Cingulum wall preparation has to be given greater emphasis as it is important in the retention and resistance of the restoration.